Magnetic field effects on the NiO magnon spectra - Milano, Julian (2010)
The effect of an external magnetic field on the eight antiferromagnetic resonance AFMR modes of NiO hasbeen studied experimentally using Brillouin light scattering. The results are reproduced by a model thatincludes the effects of exchange, dipolar coupling, a small cubic anisotropy, and Zeeman terms. Magnetic fieldsup to 7 T were applied along several NiO crystalline directions. The agreement between theory and experimentprovides additional proof that the model, recently introduced to explain the existence of the AFMR multiplet,is indeed valid. Deviations between simulations and experiments, together with a review of previously publishedresults, indicate that large magnetostrictive effects are present in NiO.